Influence of moisture content on the wave velocity to estimate the mechanical properties of large cross-section pieces for structural use of scots pine from spain - Montero, M.J.; de la Mata, J.; Esteban, M.; Hermoso, E. (Maderas. Ciencia y Tecnología, 2025)
The aim of this research is to evaluate the influence of the moisture content of wood on stress wave velocity, as a nondestructive technique for estimating the mechanical properties of gross cross-section Spanish Scots pine (Pinus sylvestris) lumber for structural use. 26 100 x 150 x 3000 mm pieces from Segovia, Spain, were tested with different moisture content values, from 35,5 to 9%. Measurements of longitudinal stress wave velocity were carried out during the natural drying process by using three commercial portable devices based on ultrasonic, acoustic and vibrational techniques. The results can be summarized as three percentage points of decreasing velocity per percentage point of increased wood moisture content in the range from 11,8 to 21,4%: 0,48% for ultrasonic, 0,50% for acoustic wave and 0,65% for longitudinal vibration.